Stability and Flow Analysis of Bituminous Concrete Grade 2 using Different Waste Materials as Additives - Randhawa, Amit (My University, 2014)
Generally a bituminous mixture is a mixture of coarse aggregate, fine aggregate, filler and binder. A Hot Mix Asphalt is a bituminous mixture where all constituents are mixed, placed and compacted at high temperature. HMA can be Dense Graded mixes (DGM) known as Bituminous Concrete (BC). Bituminous mix is generally used as a surface course and wearing course in flexible pavements since it is necessary that the wearing course must provide a smooth riding surface that is dense and at the same time take up wear and tear due to traffic. The development of transportation plays an important role in the development of nation. With flexible pavements being widely used in India, steps must be taken to increase the life of the bituminous pavements. Flexible pavements are often plagued with problems of cracking and rutting due to repeated traffic loads. Hence one needs to address these problems in order to improve the performance of flexible pavements. The project studies the suitability of waste plastic bottles, discarded tyre rubber and coconut fibres as a reinforcing material in bituminous mixes for Bituminous concrete Grade 2. Marshall method of mix design was adopted for the mixes and the optimum bitumen content are determined for bituminous mixes and their performance is analysed. The optimum binder content is calculated as 6% for 60/70 penetration grade bitumen. In this study stability and flow analysis for Bituminous Concrete Grade 2 mixture with different percentage replacement of bitumen with waste material such as waste plastic bottle , discarded tyre rubber and coconut fibres has been done. After experimental study it has been found that replacement of optimum binder content with 10% waste plastic, 6% crumb tyre rubber, 1% coconut fibre increases the stability of the mix by 10.67%, 10.37%, 10.08% respectively. Also the flow criteria as specified by the MORT&H for BC Grade 2 has been satisfied by all the additives. Out of the three additives used in the study it has been found that replacement of OBC by 10% waste plastic has the highest Marshall stability value.
ME, CED
Keywords: Stability & Flow; BC grade 2